A novel F1552/C1552 point mutation in the Aedes aegypti voltage-gated sodium channel gene associated with permethrin resistance - Jintana Yanola (2018)
Sodium channel mutations were investigated through nucleotide sequencing of three cDNA fragments amplified from permethrin resistant and susceptible Aedes aegypti from northern Thailand. There was a novel nucleotide substitution (T → G) at the second position of codon 1552 resulting in the replacement of Phenylalanine by Cysteine in segment 6 domain III. This amino acid was indicated by another study to involve an aromatic-aromatic contact between the sodium channel protein and the first aromatic ring of the pyrethroid alcohol moiety. Reciprocal crosses between the homozygous parental susceptible and resistant strains indicated that resistance was autosomal and incompletely recessive, and highly associated with the homozygous mutation. The bioassay of the F2progeny, formed by backcrossing the F1with the resistant parental strain, did not show a clear plateau curve across the range of doses, suggesting that resistance to permethrin was controlled by more than one gene locus. Other possible resistance mechanisms involved are discussed. © 2009 Elsevier Inc. All rights reserved.